Maternal serologic screening to prevent congenital toxoplasmosis: a decision-analytic economic model. - Eileen Stillwaggon; Christopher S Carrier; Mari Sautter; Rima McLeod (Public Library of Science (PLoS), 2011)
To determine a cost-minimizing option for congenital toxoplasmosis in the United States.A decision-analytic and cost-minimization model was constructed to compare monthly maternal serological screening, prenatal treatment, and post-natal follow-up and treatment according to the current French (Paris) protocol, versus no systematic screening or perinatal treatment. Costs are based on published estimates of lifetime societal costs of developmental disabilities and current diagnostic and treatment costs. Probabilities are based on published results and clinical practice in the United States and France. One- and two-way sensitivity analyses are used to evaluate robustness of results. Universal monthly maternal screening for congenital toxoplasmosis with follow-up and treatment, following the French protocol, is found to be cost-saving, with savings of $620 per child screened. Results are robust to changes in test costs, value of statistical life, seroprevalence in women of childbearing age, fetal loss due to amniocentesis, and to bivariate analysis of test costs and incidence of primary T. gondii infection in pregnancy. Given the parameters in this model and a maternal screening test cost of $12, screening is cost-saving for rates of congenital infection above 1 per 10,000 live births. If universal testing generates economies of scale in diagnostic tools-lowering test costs to about $2 per test-universal screening is cost-saving at rates of congenital infection well below the lowest reported rates in the United States of 1 per 10,000 live births.Universal screening according to the French protocol is cost saving for the US population within broad parameters for costs and probabilities.